Understanding women's experiences of their bodies after undergoing a mastectomy and not choosing reconstruction : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany Campus, New Zealand - Devlall, Thiloshini (Massey University, 2017)
The aim of the research was to explore women’s experiences of their bodies after undergoing a mastectomy due to breast cancer treatment and choosing not to have reconstruction. A qualitative study was carried out to gain a deeper understanding into women who took on a counter-cultural approach of choosing to live without breasts in a society that views breasts as the epitome of womanhood and a symbolic representation of femininity. Purposive sampling was used to meet two criteria, that is, to recruit the women who underwent mastectomies because it was part of a treatment plan to remove the cancerous tumours from their breast/s, which entailed losing one or both breasts and secondly who chose not to have reconstructive surgery after the mastectomy. In-depth interviews revealed a range of shared experiences of having breast cancer, undergoing a mastectomy and living without breasts. Data analysis was conducted using the phenomenological approach. Three leitmotifs emerged from the data: (1) Pressure for a “normal” body; the leitmotif highlighted the pressure the women experienced to conform to having two breasts. (2) Experiencing the body as transitional. Many of the women described various transitions that occurred from the time of being diagnosed, going through treatment and living with one or no breasts. (3) Exhibiting agency, the women described the various things they did to help deal with the changes they encountered. The research identifies that in the face of social pressure, perceptions of the body are transitional and that exhibition of agency is crucial amongst breast cancer survivors.
Keywords: Mastectomy; Mammaplasty; Psychological aspects; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology::Applied psychology